Validity and Realibility Test of Developed Servqual Instrument for Outpatients Pharmacy Services at Pratama Annisa Primary Healthcare Semarang - Al Farizi, Gilang Rizki; Gloria, Fransisca; Maula, Vita Zulfatul (Science and Community Pharmacy Journal, 2022)
The quality of pharmaceutical care services has an important role and main indicator for valuation the National Health Insurance (JKN). Patient satisfaction is the goal of pharmaceutical care services that serve to improve the quality of life of patients. Servqual is a method that has often been used to measure service satisfaction. The development of servqual instruments could be deploved to the needs of services in the pharmaceutical sector to maintain service quality . This study was conducted to measure the validity and reliability test of the Indonesian version of the developed servqual instrument for outpatient pharmacy services at Pratama Annisa primary healthcare Semarang. This study was an observational method through an analytic survey with a cross-sectional approach. The number of samples was 40 outpatients using the purposive sampling technique. The validity test was performed using the Aiken V index (≥ 0,4) and construct study. Reliability test used the internal consistency technique (Cronbach alpha coefficient ≥ 0,6). The result of the validity test showed that the correlation value of each item was > 0.4 and the reliability test result showed that the Cronbach alpha coefficient was 0.932. The Developed of servqual instrument is valid and reliable for measuring the costumer satisfaction